Case Report: Long-Term Treatment and Follow-Up of Kleefstra Syndrome-2 - Wu, Dandan; Li, Rong (Frontiers in Pediatrics, 2022)
Background: Mutations in the KMT2C gene can cause Kleefstra syndrome-2 (KLEFS2). Case: In this study, we analyzed the clinical, genetic testing and 10-year follow-up data of a child with KLEFS2 treated at the Children Healthcare Department, Children’s Hospital of Nanjing Medical University. The case of KLEFS2 presented feeding difficulty and developmental delay, both intervened by nutritional support and family rehabilitation. Obvious attention deficit hyperactivity disorder (ADHD) occurred in preschool and school age, and was managed by behavioral and pharmaceutical interventions. Conclusion: Features of KLEFS2 include feeding difficulty and developmental delay in the early age, and ADHD in preschool and school age. Satisfactory outcomes are not achieved in early nutritional support for correcting malnutrition and pharmaceutical intervention for relieving ADHD, but both measures can counter developmental delay.